"Think bigger about science": Using Twitter for learning in the middle grades. Issue 3 (26th May 2016) - Becker, Ryan; Bishop, Penny
Abstract: This article examines the use of Twitter as a learning tool in a middle grades science classroom. Relevant research, the direct experience of the teacher leading this unique initiative, and the invaluable perspectives of his middle level students are included to inform interested stakeholders. Following a discussion of open versus closed digital environments, a rationale for why open forms of social media, like Twitter, can be appropriate for middle grades students is explored. The ways in which one author integrates Twitter into his teaching is then described before student outcomes are explained, including the voices and perspectives of students themselves. Finally, the challenges teachers might face in using Twitter with students are discussed and recommendations are offered for those considering integrating social media into their pedagogy.